Nilai Moral yang Terkandung Dalam Cerita Rakyat Pada Ibuku Tradisi Lisan Sang Penutur oleh Fadlan Harun - Burhanudin, Yunita Sari; Taha, Nasim; S, Safira; Muno, Intan Wahyuni; Wahyuni, Wiwik (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This study aims to analyze the moral values contained in folklore, especially in the story of the Tobelo War and the Tale of Tapilaya and Bolotogoa which are listed in the book Tradisi Oral Sang Penutur. The formulation of the problem in this study is: What are the moral values contained in the story of the Tobelo War and the Tale of Tapilaya and Bolotogoa? This study uses a descriptive qualitative approach with data collection techniques through literature studies. Data were obtained from the book Tradisi Oral Sang Penutur by Fadlan Harun which contains these folklores. The main informant in this study is the story text which is analyzed to explore the moral values contained therein. The results of the study indicate that in both folklores there are social moral values, individual moral values and religious moral values, various moral values that can be used as guidelines for life. In the story of the Tobelo War, there are twenty-four social morali valuesi, two individual moral values and one morali valuei, while in the Tapilaya and Bolotogoa Stories, there are five sociali morali valuesi, one individual moral value and two religious morali valuesi. In addition, these two stories also emphasize the moral values of human relationships with other humans, human relationships with themselves and human relationships with God or what is believed in.